Gastric carcinogenesis in the rat induced by duodenogastric reflux without carcinogens: morphology, mucin histochemistry, polyamine metabolism, and labelling index. Issue 12 (December 1991) - Taylor, P R; Mason, R C; Filipe, M I; Vaja, S; Hanley, D C; Murphy, G M; Dowling, R H; McColl, I
Abstract : Chronic duodenogastric reflux induces gastric adenocarcinomas in the rat without the use of carcinogens. Altogether, 186 male Wistar rats were randomised to undergo either a simple gastrojejunostomy or a gastrotomy and sacrificed at eight weekly intervals for 56 weeks. No control animals developed dysplasia or carcinoma. All rats subjected to a gastrojejunostomy showed hyperplasia of the proliferative neck zone, with increased sulphomucin production adjacent to the scar. Low grade dysplasia was found at 16 weeks, and carcinoma was first seen at 32 weeks. Most carcinomas were well differentiated mucin secreting adenocarcinomas of the expanding type, which secreted a mixture of sialomucins and sulphomucins. Duodenogastric reflux was associated with a 100% increase in labelling index (assessed autoradiographically with tritiated thymidine) in the gastric mucosa when compared with corresponding tissue adjacent to a gastrotomy scar. This increase was significant at eight weeks and persisted for 56 weeks after surgery. This study supports the theory that, in this model, hyperplasia precedes the development of carcinoma.